Energy transfer in (PEA)2FAn−1PbnBr3n+1 quasi-2D perovskites. Issue 14 (26th March 2021) - Litvinas, Džiugas; Aleksiejūnas, Ramūnas; Ščajev, Patrik; Baronas, Paulius; Soriūtė, Vaiva; Qin, Chuanjiang; Fujihara, Takashi; Matsushima, Toshinori; Adachi, Chihaya; Juršėnas, Saulius
Abstract : Simultaneous fast energy funnelling between the neighbouring sheets and slower carrier and exciton in-plane diffusion revealed in quasi-2D perovskites. Abstract : Quasi-two dimensional perovskites demonstrate unique excitonic properties due to their multilayer structure making them attractive for various optoelectronic applications. However, the thickness of individual perovskite sheets in wet cast quasi-2D layers tends to randomly fluctuate giving rise to a specific type of disorder, which impacts on the carrier dynamics and is rather complex and remains understudied. Here, we present a study of carrier transport in Ruddlesden–Popper type (PEA)2 FA n −1 Pb n Br3 n +1 layers of order n from one to four, and in the bulk FAPbBr3 layer. We use a light induced transient grating technique to measure the carrier diffusion coefficient directly, and the transient absorption via photoluminescence to investigate the energy relaxation pathways. We observe two distinct energy transfer processes on different time scales. Fast energy funnelling in thicker ( n ≥ 3) layers is observed up to 10 ps after excitation; we attribute this to short-distance transfer of excitons to neighbouring perovskite sheets of higher order. On the longer timescale of hundreds of picoseconds, carrier in-plane transport is governed by exciton diffusion in n = 1 and 2 layers and by free carrier plasma in thicker ones. Within the carrier density range of (0.5–4) × 10 19 cm −3, the exciton diffusion coefficient in n = 1, 2 increases slowly from 1 to 2.8 cm 2 s −1, whereas in thicker layers the dependence is much stronger and the diffusivity grows from 0.09 to 1.9 cm 2 s −1 . We explain these dependencies by a higher structural order in the thinner samples and the stronger localization of carriers in thicker ones. Also, amplified spontaneous emission (ASE) is observed in thicker ( n ≥ 3) layers in electron–hole plasma, as evidenced by the typical ASE line redshift upon excitation.